Journal of management, spirituality & religion (Routledge, Taylor and Francis Group, 2004)
The journal provides a forum to scholars engaged in the study of work and organizations, and in particular management, on issues pertaining to spirituality and religion as these affect all and any aspects of management, organizing, and work. The journal aspires to become a hub for the generation of knowledge and a forum for the exchange of ideas and debate, as well as an information base on pertinent events, new books, upcoming conferences, etc.